Screening of Antibacterial Activity of Ethyl Acetate Fraction of Eleutherine palmifolia (L.) Merr Bulbs against Salmonella typhi - Siti Rofida; Ahmad Shobrun Jamil; Nurul Amalia Azhari (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2020)
Typhoid fever is an infection caused by the bacterium Salmonella typhi, spread through contaminated food or water. Typhoid fever can be treated with antibiotics, but at this time some pathogen microbes have been resistant to the available antibiotics. Antimicrobials derived from natural product might be the alternative to overcome antibiotic resistance. Eleutherine palmifolia (L.) Merr is empirically used to treat infectious diseases. E. palmifolia has chemical compounds of alkaloids, glycosides, flavonoids, phenolics, steroids, and tannins. This study aims to evaluate the antibacterial activity of ethyl acetate fraction against S. typhi. E. palmifolia bulbs were subsequently extracted using n-hexane solvents and followed by ethyl acetate solvents. The ethyl acetate fraction was tested for antibacterial activity using the disc diffusion method. The ethyl acetate fraction of E. palmifolia at the concentrations of 8, 6, and 8 mg/paper disc showed the diameters of the inhibition zone of 15.1±3.6, 15.3±3.3, and 16.9±1.9 mm, respectively. The conclusion of this study was the ethyl acetate fraction of E. palmifolia has a strong antibacterial activity against S. typhi.